AB0460 Long-term remission with golimumab in active rheumatoid arthritis patients despite methotrexate through 2 years. (23rd January 2014) - Keystone, E.; Genovese, M.; Klareskog, L.; Xu, S.; Han, C.; Hsia, E.
Abstract : Objectives: To assess long-term remission through 2 yrs from GO-FORWARD. Methods: Retrospective analysis of GO-FORWARD (RA pts with inadequate response to MTX) thru Wk104. Active RA (N=444) pts despite MTX were random'd to PBO+MTX, GLM100mg+PBO, GLM50mg+MTX, or GLM100mg+MTX, Pts with <20% improvmnt in SJC/TJC at wk16 entered EE: PBO+MTX$→ $GLM50mg+MTX, GLM 100mg+PBO$→ $GLM100mg+MTX, GLM 50mg+MTX$→ $GLM100mg+MTX. At Wk24, pts on PBO+MTX, crossed over to GLM 50mg+MTX. GLM/PBO was inj q4wks. Remission rates at Wk24, and the propor who remained in remission at Wks52&104 were assessed using 4 def'n: DAS28 (weighted sum of SJC/TJC, 28 joints, CRP, and ptGA); EULAR Boolean(DefA) TJC/SJC, 28 joints, CRP mg/dL, and ptGA, each score ≤1; EULAR SDAI (Def B)-SDAI score is sum of TJC/SJC, 28 joints, ptGA, phyGA, and CRP mg/dLwith scoring ≤3.3; and CDAI (sum of SJT/TJC, 28 joints, ptGA, phyGA ≤2.8). Among those who didn't achieve remission at Wk24, propor of pts who later achieved remission at Wks52&104 using each def are presented. Observed data was used. Results: At Wk24, sig greater propor of pts achieved remission in the GLM+MTX grps vs PBO+MTX(Table1). At Wk52, ∼80% of pts in the GLM+MTX grp remained in remission using DAS28, SDAI, and CDAI;∼70% remained in remission using Boolean def. At Wk104, among those GLM+MTX pts who achieved remission at Wk24, the propor of pts with sustained remission were: DAS 28 ∼90%, Boolean def ∼55%, and SDAI and CDAI∼65% each. Approx 20% of pts who didn't achieve remission at Wk24, did achieve remission at Wks52&104, with higher rates using DAS28∼30%, and slightly lower rates using Boolean def∼15%. Conclusions: Using any of 4 remission criteria, GLM+MTX induced remission in a greater propor of pts than PBO+MTX and remission was sustained in the majority of those pts through yrs1 and 2. Disclosure of Interest: E. Keystone Consultant for: Janssen Research & Development, Inc, M. Genovese Consultant for: Janssen Research & Development, Inc, L. Klareskog Consultant for: Janssen Research & Development, Inc, S. Xu Employee of: Janssen Research & Development, Inc, C. Han Employee of: Janssen Research & Development, Inc, E. Hsia Employee of: Janssen Research & Development, Inc